The Supply Chain Maze: The Struggles of Small and Medium Enterprises and Ways to Navigate the Challenges - Natesh Kumar, Nitin (ExcelingTech, 2025)
Small and Medium Enterprises (SMEs) face significant challenges in managing supply chains due to fragmented communication, limited resources, and outdated technologies. Without a centralized platform, inefficiencies arise, leading to missed deadlines, inaccurate inventory levels, and supply- demand mismatches. This article explores these challenges and presents strategies to enhance SME resilience and profitability. By adopting modern SCM technologies such as cloud-based systems, real-time tracking, and predictive analytics, SMEs can improve operational efficiency and decision-making. Diversifying supplier relationships and leveraging trade finance solutions can help mitigate risks and ensure financial stability. Additionally, outsourcing logistics and customer service can reduce operational burdens while sustainability initiatives offer long-term cost savings and market competitiveness. Implementing these strategies will not only strengthen SME supply chains but also support policymakers in formulating practical measures to enhance business resilience in an increasingly complex global economy.